Natural rate doubts - Andreas Beyer; Roger E. A. Farmer (European Central Bank (ECB), 2002)
We study the low frequency comovements in unemployment, inflation and the federal funds rate in the U.S. From 1970 through 1979 all three series trended up together; after 1979 they all trended down. The conventional explanation for the buildup of inflation in the 1970's is that the Fed reacted to an increase in the natural rate of unemployment by conducting an overly passive monetary policy. We show that this explanation is difficult to reconcile with the observed comovement of the fed funds rate and inflation. We argue instead that the source of the inflation buildup in the 1970's was a downward drift in the real interest rate that was translated into a simultaneous increase in unemployment and inflation by passive Fed policy. Our explanation relies on the existence in the data of an upward sloping long run Phillips curve.
Keywords: C32; E3; E43; E58; 330; Natural rate; Phillips curve